THE DETERMINATION OF THE SPECIFIC VOLUME OF STATIC CONVERTERS OF ASYNCHRONOUS TRACTION DRIVE - Muha, A. M. (Science and Transport Progress, 2008)
Issues of determination of the specific volume of steady-state converters for multi-system electric rolling stock of railways are discussed in the article.